# Evaluate the trigonometric sum sin(pi/3)+sin(2pi/3)+sin(3pi/3)+sin(4pi/3) . Since this trigonometric sum involves the angles that are multiples of pi/3 (equivalent to 60 degrees)—a "special" angle with known sine, cosine, and tangent values—each of the terms can be evaluated separately.

• pi/3 is an acute angle located in the first quadrant, and it has a known sine value: sin(pi/3)...

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Since this trigonometric sum involves the angles that are multiples of pi/3 (equivalent to 60 degrees)—a "special" angle with known sine, cosine, and tangent values—each of the terms can be evaluated separately.

• pi/3 is an acute angle located in the first quadrant, and it has a known sine value: sin(pi/3) = sqrt(3)/2

• 2pi/3 is located in the second quadrant, so its sine value is positive and equal to that of pi/3: sin(2pi/3) = sqrt(3)/2

• 3pi/3 = pi. This is a quadrantal angle, located on the x-axis, so its sine is zero: sin(3pi/3) = 0

• 4pi/3 is located in the third quadrant, so its sine value is negative and equal to the opposite of that of pi/3: sin(4pi/3) = -sqrt(3)/2

Adding it all together, we get sqrt(3)/2 + sqrt(3)/2 + 0 + (-sqrt(3)/2) = sqrt(3)/2.

The value of the trigonometric sum is sqrt(3)/2.

Approved by eNotes Editorial Team We have to find the result of sin(pi/3) + sin(2pi/3) + sin(3pi/3)  + sin(4pi/3)

We use sin (pi/3) = (sqrt 3)/2

sin (2*pi/3) = sin (pi - pi/3) = sin (pi/3) = (sqrt 3)/2

sin (3*pi/3) = sin (pi) = 0

sin (4*pi/3) = sin (pi/3 + pi) = -sin (pi/3) = -(sqrt 3)/2

Adding  (sqrt 3)/2 + (sqrt 3)/2 + 0 - (sqrt 3)/2

=> (sqrt 3)/2

The required sum of sin(pi/3) + sin(2pi/3) + sin(3pi/3)  + sin(4pi/3) = (sqrt 3)/2

Approved by eNotes Editorial Team